Essays on fiction 1971-82 - Kermode, Frank (Routledge revivals., 2015)
In this book, which was first published in 1983, Frank Kermode looks in particular at the revived Russian Formalism, a highly original body of literary theory that flourished in the years immediately following the Revolution, and at the work of Roman Jakobson, one of its most distinguished exponents. He discusses its modern 'structuralist' descendants, recalling the importance of Roland Barthes and the invigorating effect of his fertile and surprising mind. He considers also the work of Foucault, Laca and Levi-Strauss, as well as that of Jacques Derrida, which uses a novel and de(con)structive.